Histopathological insights into hair loss in Cronkhite–Canada syndrome: Diffuse anagen‐telogen conversion precedes clinical hair loss progression. (29th May 2013) - Watanabe‐Okada, Emiko; Inazumi, Toyoko; Matsukawa, Hidehiko; Ohyama, Manabu
Abstract Cronkhite–Canada syndrome (CCS) is a rare disorder characterised by gastrointestinal polyposis and ectodermal changes, represented by extensive alopecia. Detailed histopathological investigations of alopecic lesions in two female CCS patients with severe hair loss revealed a marked increase in telogen hair follicles with no sign of loss or of the minaturisation or atrophy of hair follicle structures and the absence of inflammatory change, despite severe inflammation in the gastrointestinal tract. These findings suggested that hair regrowth can be expected without systemic corticosteroids, if they are not necessary for treatment of the gastrointestinal tract, and that anagen‐telogen transition is an early event preceding clinical hair loss in CCS.